Impedance technique for monitoring of apatite precipitation from simulated body fluid. (1st May 2018) - Fojt, Jaroslav; Joska, Ludek; Hybasek, Vojtech; Pruchova, Eva; Malek, Jaroslav
Abstract: In vitro testing of bioactivity of metallic materials is frequently executed in simulated body fluid. Measurements are usually used as yes/no test. Samples are removed after some time of exposure from the environment and the level of bone-like apatite precipitation is evaluated. The goal of the presented study was to determine the ability of electrochemical techniques to detect changes on the phase boundary with sufficient sensitivity. The behaviour of Ti-35Nb-2Zr-0.2O alloy with modified surfaces was studied in this work. Nanotubes with three different diameters were prepared by anodic oxidation. Modified surfaces were described in the terms of morphology and chemical composition. Specimens were exposed to simulated body fluid and apatite precipitation was monitored. The electrochemical impedance spectroscopy was used for the nanotubes – electrolyte phase boundary changes description. Measurement at constant frequency was used for determination of the apatite precipitation. The surface analysis indicated enrichment of the nanotubular layer by niobium. The exposure in simulated body fluid resulted in apatite layer creation on the nanotubes with the largest diameter only. The changes on phase boundary were clearly detected by electrochemical impedance spectroscopy in a broad range of frequencies, constant frequency impedance measurement allowed for the determination of incubation period. Highlights: Nanotubular oxide structures were prepared on beta titanium alloy. Impedance spectroscopy is useful for apatite formation monitoring. Larger tubes diameter support apatite precipitation.